In the air and on the streets: Pajubá and humor among transvestites from a city in são paulo state - Brancaleoni, Ana Paula Leivar [UNESP]; Kupermann, Daniel (My University, 2021)
This work aims to discuss the making of humor among transvestites who experience conditions of high social vulnerability, with special emphasis on the“pajubá”, a dialect initially used among transvestites and later also appropriated by other groups in the LGBTT+ universe. We will use excerpts from interviews and situations observed, from an ethnographic perspective, during fieldwork with a group of transvestites from a city in São Paulo state, as well as cultural productions that invite us to reflect on the issue. Psychoanalysis is included as a proposed theoretical interlocution. Several dimensions of humor are identified: The production of modes of sociability; depathologization of travestilities; indication of the performative character of gender binarism; transformation of anguish into laughter, celebration of life. Through laughter, transvestites also assert themselves as subjects who do not resign themselves to suffering, who do not succumb to an unfavorable and exclusionary reality.
En el aire y en las calles: Pajubá y humor entre travestis del interior de São Paulo
No ar e nas ruas: Pajubá e humor entre travestis do interior de São Paulo
Keywords: Gender identity; Humor; Pajubá; Psychoanalysis; Transvestites